The Social and Political History of Southern Africa's Languages (Palgrave Macmillan UK, 2018)
This book is the first to offer an interdisciplinary and comprehensive reference work on the often-marginalised languages of southern Africa. The authors analyse a range of different concepts and questions, including language and sociality, social and political history, multilingual government, and educational policies. In doing so, they present significant original research, ensuring that the work will remain a key reference point for the subject. This ambitious and wide-ranging edited collection will appeal to students and scholars of southern African languages, sociolinguistics, history and politics. Tomasz Kamusella is Reader at the University of St Andrews, UK. He specializes in language politics and nationalism and has published widely on the topic, including The Palgrave Handbook of Slavic Languages, Identities and Borders (Palgrave Macmillan, 2016). Finex Ndhlovu is Associate Professor at the University of New England, Australia. His research specialisms include contemporary linguistic and sociocultural theories of language, identity and sociality in relation to African diaspora communities. His most recent major publication is Becoming an African Diaspora in Australia (Palgrave Macmillan, 2014). .